Population biology of mountain plovers in southern Phillips County, Montana - Dinsmore, Stephen J., author; White, Gary C., advisor (Colorado State University. Libraries, 2001)
Effective conservation measures for rare or declining species cannot be implemented unless their biology and demography are well understood. The Mountain Plover (Charadrius montanus) is a local and declining species breeding on the western Great Plains of North America. Populations are thought to have declined drastically in the last several decades and the species has been proposed to be listed as Threatened. Their breeding biology has been extensively studied, especially in northeastern Colorado, although aspects of their life-history such as their demography have not been studied. During a 6-year study (1995-2000) I investigated their nesting biology, demography, and population trends in southern Phillips County, Montana. I modeled the daily nest survival of Mountain Plovers as a function of the sex of the incubating adult, daily nest age, year, linear and quadratic time trends, and two weather covariates (maximum daily temperature and daily precipitation). The sample of 432 nests included slightly more male-tended nests (55% of total). Observed (31 May for females and 2 June for males) and expected (27 May for females and 26 May for males) mean nest initiation dates did not differ between nests tended by female and male plovers. I found that daily nest survival was a function of the sex of the incubating adult, daily nest age, a quadratic time trend, and daily precipitation. I found no evidence of yearly differences or an effect of maximum daily temperature on nest survival. Nests tended by male plovers had higher daily survival rates than those tended by females. Daily nest age positively influenced survival with older nests having higher survival, although this effect may have been confounded with individual heterogeneity. Daily precipitation during the nesting season negatively influenced nest survival. Seasonally, the daily survival of Mountain Plover nests was high early in the nesting season, dipped to a low in mid-season, and then gradually rose to a peak at the end of the nesting season. Total nesting success was 0.35 for nests tended by females and 0.49 for nests tended by males. I used the robust design in program MARK to estimate annual apparent survival (ϕ), conditional capture (p and r) and recapture (c) probabilities, and the annual population size (N) of Mountain Plovers in southern Phillips County, Montana in the presence of temporary emigration. I modeled annual survival rates as a function of two age classes (adults and juveniles), body mass at capture (juveniles only), a radio transmitter effect in 1999, and annual area occupied by prairie dogs within the study area. I modeled year-specific capture probabilities to include a resighting effect (r) for plovers that had been marked in a prior year. The results supported age-specific differences in annual survival that were also a function of juvenile body mass and area occupied by prairie dogs. Body mass had a positive effect on juvenile survival. The area occupied by prairie dogs appeared to have no effect on survival. Estimated annual apparent survival rates were 0.46 to 0.49 for juveniles and 0.68 for adult plovers. Using these estimates, I computed the mean life span of a Mountain Plover at banding as 1.92 years (SE = 0.17; 95% Cl was 1.58, 2.26). There was strong evidence for a negative resighting effect on capture probabilities. The size of the adult Mountain Plover population in the study area was estimated at between 95-180 individuals annually. The population size closely tracked annual changes in the area occupied by black-tailed prairie dogs with both prairie dogs and plovers rapidly recovering from an outbreak of sylvatic plague in the mid-1990s. Finally, I estimated the annual rate of population change (λ) and recruitment rate (ƒ) using the Pradel models. I modeled λ as a constant across years, as a linear time trend, as year-specific, and as a function of the area occupied by prairie dogs. I modeled ƒ only as a function of the area occupied by prairie dogs. The results indicated a strong negative effect of area occupied by prairie dogs on both λ and ƒ. There was also good evidence for a negative time trend on λ; this model had substantial weight (wi = 0.31) compared to models without a time trend. Yearly estimates of λ were >1 in all years except 1999, indicating that the population increased beginning in 1995 and then stabilized in the last year of the study. There was weak evidence for year-specific estimates of λ; the best model with year-specific estimates had a low weight (wi = 0.02), although the pattern of yearly estimates of λ. closely matched those estimated with a linear time trend. I found that the population trend of Mountain Plovers closely matched the trend in the area occupied by black-tailed prairie dogs. Black-tailed prairie dogs declined sharply in the mid-1990s in response to an outbreak of sylvatic plague, but their numbers steadily increased since 1996 with subsequent increases in plovers. This suggests that the conservation of Mountain Plovers in this region is closely linked to the available area occupied by prairie dogs. Threats to prairie dogs such as sylvatic plague and recreational shooting pose indirect threats to Mountain Plovers.
Keywords: ecology